Extreme eutrophication and salinisation in the Coorong estuarine-lagoon ecosystem of Australia's largest river basin (Murray-Darling). (March 2023) - Mosley, L.M.; Priestley, S.; Brookes, J.; Dittmann, S.; Farkaš, J.; Farrell, M.; Ferguson, A.J.; Gibbs, M.; Hipsey, M.; Huang, J.; Lam-Gordillo, O.; Simpson, S.L.; et al.
Abstract: Estuaries in rainfall poor regions are highly susceptible to climatic and hydrological changes. The Coorong, a Ramsar-listed estuarine-coastal lagoon at the end of the Murray-Darling Basin (Australia), has experienced declining ecological health over recent decades. Twenty years of environmental data were analysed to assess patterns and drivers of water quality changes. Large areas of the Coorong are now persistently hyper-saline (salinity >80 psu) and hypereutrophic (total nitrogen, TN > 4 mg L −1, total phosphorus, TP > 0.2 mg L −1, chlorophyll a  > 50 μg L −1 ) which coincided with reduced flushing due to diminished freshwater inflows and increasing evapo-concentration. Sediment quality also was related to flushing, with higher concentrations of organic carbon, TN, TP and sulfides as salinity increased. While total nutrient levels are very high, dissolved inorganic nutrients are generally low. Increased lagoonal flushing would be beneficial to reduce the hypersalinisation and hypereutrophication and improve ecosystem health. Graphical abstract: Unlabelled Image Highlights: The Ramsar-listed Coorong estuary is experiencing declining ecological health. Extreme eutrophication has intensified with persistent hypersalinity. Nutrients increase with salinity increase in both water and sediment. Loss of aquatic plants and macroinvertebrates has exacerbated eutrophication. Increased flushing would be beneficial to improve water quality and ecosystem health.